Efektivitas Media Video Dan Leaflet Terhadap Minat Melaksanakan Senam Hamil Pada Ibu Hamil - Helisusanto, Rinda Handayani; Wiyadi, Wiyadi; Raihanah, Siti (Akademi Kebidanan Bunga Husada Samarinda, 2023)
MMR and IMR are among the key indicators of a country's state of health. Pregnancy exercise in antenatal class is a health program aimed at reducing maternal and fetal morbidity and mortality. The use of appropriate media is essential to convey health education about exercise during pregnancy to the general public. A good quality video and leaflet will provide enough knowledge to increase interest in performing exercises during pregnancy. The aim of this study was to determine the effectiveness of videos and leaflets on the benefits of performing exercises during pregnancy for pregnant women at the Public Health Center in Menamang Kanan Village. Methods This research method is semi-empirical. The population includes pregnant women in the working area of ​​the public health center in Menamang Kanan village. Sampling technique with a total sample of 30 people. The results showed that there was a significant difference in interest in doing exercises during pregnancy after receiving the videos and leaflets (p value = 0.004) with a value of α = 0.05. Accuracy in media selection will support the effectiveness of health education activities carried out. The video provides a real-life experience for pregnant women as they can directly see and hear what is being studied. By unfolding, the presentation of the material is less enjoyable and the absorption is less obtained than the delivery of the material by video. This video is more effective than leaflets in increasing the interest of pregnant women in pregnancy exercise at the public health center in Menamang Kanan village